MUTHAWWIF COMPETENCY IMPROVEMENT TRAINING IN THE SERVICE OF HAJJ AND UMRAH PILGRIMS IN SAUDI ARABIA - Intan Nurrachmi; Neni Sri Imaniyati; Panji Adam Agus Putra (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Training is one of the crucial elements in strengthening the professional capabilities of Muthawwif, a spiritual and practical companion for Hajj and Umrah pilgrims in Saudi Arabia. This PKM explores the significance of training in improving the competence of Muthawwif, focusing on improving services and pilgrim experience. Effective training methods integrate key aspects, including religious knowledge, time management, intercultural communication, as well as emergency situation handling skills. Analysis of the training results shows a marked improvement in the quality of services provided by Muthawwif, as well as its positive influence on pilgrim satisfaction and safety. The implications of this increased competence pave the way for further development in supporting spiritual and safety experiences for Hajj and Umrah pilgrims in Saudi Arabia.